2012
DOI: 10.1007/s10620-012-2089-4
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Thioredoxin Family Proteins and Proliferation Markers in Dysplastic and Malignant Gallbladders in Patients with Primary Sclerosing Cholangitis

Abstract: PSC patients have a frequency of gallbladder dysplasia/carcinoma of 30% in operative specimens. The overexpression of TrxR1-v2,3,5 and down regulation of Grx1 in dysplastic gallbladder epithelium suggest that these proteins should be further evaluated as possible future immunohistochemical markers in the early diagnosis of biliary malignancy in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…In this regard, 2 patients exhibiting high grade dysplasia had a pre-operative diagnosis of primary sclerosing cholangitis, a known risk factor for gallbladder malignancy with previous reports of up to 30% of resected gallbladders displaying dysplasia/carcinoma pathology[17]. Consistent with this, our policy is to adopt a low threshold in recommending cholecystectomy in patients with primary sclerosing cholangitis presenting with clinical or radiological evidence of gallbladder pathology.…”
Section: Discussionsupporting
confidence: 69%
“…In this regard, 2 patients exhibiting high grade dysplasia had a pre-operative diagnosis of primary sclerosing cholangitis, a known risk factor for gallbladder malignancy with previous reports of up to 30% of resected gallbladders displaying dysplasia/carcinoma pathology[17]. Consistent with this, our policy is to adopt a low threshold in recommending cholecystectomy in patients with primary sclerosing cholangitis presenting with clinical or radiological evidence of gallbladder pathology.…”
Section: Discussionsupporting
confidence: 69%
“…All of the three cases with metastatic disease in our study showed Cyclin D1 expression suggesting a positive relation between tumor metastasis and Cyclin D1 expression (x 2 =5.114, p value=0.024, R=0.452, p value=0.012). Our results are in line with those of Said et al (2012) for Cyclin D1.…”
Section: F I G U Re 2 P H O T O M I C Ro G R a P H S H O W I N G P 1supporting
confidence: 92%
“…In those patients with benign masses, 33% had associated epithelial dysplasia, while in patients with primary GBC, 57% had associated dysplasia [126]. In another study, gallbladder dysplasia/carcinoma was found in 30% of operative specimens, and evidence of inflammation and fibrosis of the gallbladder wall was found in nearly half of gallbladder dysplasias and carcinomas, respectively [127]. As exemplified by PSC, autoimmune diseases probably increase risk of GBC via exacerbation of biliary inflammation.…”
Section: Other Inflammatory Pathologies That Predispose To Gallbladdementioning
confidence: 99%